(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A new series of 5-sustituted-3-((2-(4-nitrophenyl) Thiazol-4-yl) Imino)-1-(substituted-1-ylmethyl) Indolin-2-one derivatives (3a-3l) are synthesized by conventional method. All synthesized compounds were characterized via IR, 1H-NMR, 13C-NMR and MASS spectral analysis. Compounds were evaluated for their anticancer activity against MCF-7 cell lines and antibacterial activity against Staphylococcus aureus, Bacillus subtilis, E. coli and Salmonella paratyphi. These results indicated that compound 3a, 3e, 3f and 3j showed good activity compared to the standard drug. Synthesized target molecules exhibited anticancer activity against breast cancer cell lines with IC50 values of range from 60.21. to 130.21 μg. Compound 3c (60.21μg) showed good activity compared with doxorubicin. Compounds were subjected to molecular docking studies with estrogen receptor (ER) epidermal growth factor receptor (EGFR) with PDB ID:3ERT. Among the docked ligands, compound 3a and 3e reported highest docking score (-8.512, -6.869) with glide binding energy (-43.785, -24.187).